Interaction of physical activity, diet, health locus of control and quality of life among Finnish university students - Minhas, Muhammad (2013)
Muhammad Tayyab Minhas, 2013. Interaction of Physical Activity, Diet, Health Locus of Control and Quality of Life among Finnish University Students. Master’s Thesis in Sport and Exercise Psychology. Department of Sport Sciences, University of Jyväskylä, Finland.